2001
DOI: 10.1007/bf03401838
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1 Localizes to Detergent-insoluble Microdomains Within Lymphocyte Membranes

Abstract: This study identifies, for the first time, the localization of p27 within a membrane microdomain associated with signaling. Because some cell surface signaling complexes lose p27Kip1 upon cellular activation, p27Kip1 may play a functional role in modulating membrane signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In rat hepatocytes, Cdk2 has been reported to modulate receptor activation at the plasma membrane by regulating endocytosis (Gaulin et al, 2000). We have shown that the cdk2-inhibitor p27 also may interact with signaling complexes by localizing to lipid rafts (Yaroslavskiy et al, 2001) Such localization could facilitate 'inside-out' signaling of cell cycle regulators to alter signal transduction at the membrane. Indeed, recent reports that Stat3 localizes to rafts (Sehgal et al, 2002) and that stat3 undergoes endocytosis during signaling (Bild et al, 2002) indicate that Stat3 may share topographic proximity with cdk2 and cdk2 inhibitors at the cell membrane.…”
Section: Discussionmentioning
confidence: 95%
“…In rat hepatocytes, Cdk2 has been reported to modulate receptor activation at the plasma membrane by regulating endocytosis (Gaulin et al, 2000). We have shown that the cdk2-inhibitor p27 also may interact with signaling complexes by localizing to lipid rafts (Yaroslavskiy et al, 2001) Such localization could facilitate 'inside-out' signaling of cell cycle regulators to alter signal transduction at the membrane. Indeed, recent reports that Stat3 localizes to rafts (Sehgal et al, 2002) and that stat3 undergoes endocytosis during signaling (Bild et al, 2002) indicate that Stat3 may share topographic proximity with cdk2 and cdk2 inhibitors at the cell membrane.…”
Section: Discussionmentioning
confidence: 95%
“…Cytoplasmic displacement/sequestration of p27 Kip1 has been reported to be a potential mechanism of its inactivation (Barnouin et al , 1999). More recently, p27 Kip1 has been associated with detergent‐insoluble microdomains of lymphocyte membranes, known as rafts, which are thought to provide a scaffold for signalling proteins (Yaroslavskiy et al , 2001). As the localization of proteins within raft structures is thought to be important for cell signalling, it is likely that the localization of p27 Kip1 in these structures have a significant impact in the cell's response to signalling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that TNFR1 needs to be recruited to lipid rafts in order to mediate NFκB activation and that any interference with the lipid raft organization may switch TNF-signaling from NFκB activation to apoptosis in the human fibrosarcoma cells (42). Interestingly, membrane rafts in normal lymphocytes were also reported to contain p27 Kip1 , and it was suggested that p27 Kip1 may play a role in modulating membrane signaling, since it was excluded from the rafts upon lymphocytes activation (43). By taking these two together, it would be tempting to speculate that in Adp27-infected PC-3 cells, p27 Kip1 remains in lipid rafts thus preventing the activation of NFκB, and promoting the signaling to apoptosis.…”
Section: Discussionmentioning
confidence: 99%